Intra‐articular administration of antibiotics in horses: Justifications, risks, reconsideration of use and outcomes. (21st September 2021) - Pezzanite, Lynn M.; Hendrickson, Dean A.; Dow, Steven; Stoneback, Jason; Chow, Lyndah; Krause, Danielle; Goodrich, Laurie
Abstract: Antibiotics have been injected intra‐articularly by equine veterinarians for decades, either prophylactically when other drugs are administered for osteoarthritis or therapeutically to treat septic arthritis. This route of administration has also more recently gained attention in human orthopaedic clinical practice, particularly as an alternative to systemic antibiotic administration to treat infections following prosthetic arthroplasty. While the rationale for injecting antibiotics intra‐articularly has been largely focused on achieving high local drug concentrations, there has been relatively little focus on pharmacokinetic parameters of antibiotics administered by this route, or on the potential for local toxicity. The increasing incidence of antibiotic resistance in veterinary and human medicine prompts reconsideration of off‐label antibiotic usage and evaluation of evidence‐based dosing strategies. The purpose of this review was to summarise the current literature describing intra‐articular antibiotic usage, including specific studies where pharmacokinetics, potential safety and toxicity have been evaluated. This review will advance practitioners' understanding of the use of intra‐articularly administered antibiotics, including the overall pros and cons of the approach.